Sweet and Salty Recipes: Some Examples from the Muslim and Byzantine Culinary and Medicinal Common Tradition - Anagnostakis, Ilias (Studia Ceranea, 2024)
This paper discusses the use of salt, vinegar, honey, and sugar in some Byzantine and Arabic-Islamic recipes in cooking and pastry-making as well as for food preservation and in medical preparations. It draws mostly on information provided by Byzantine sources and Arabic translations for any comparison. The research focuses on some examples of salty/sour and sweet culinary and medicinal recipes, common or similar Arabo-Byzantine products like iṭriya, garos/murrī, zoulapion mishmishiyya, and libysia. The paper starts with Galen’s Syrian mēloplakous, continues with salty and sweet liquid preparations as well as preserves of roses and fruits. It concludes with a discussion of two exemplary Arabic delicacies more widely known in twelfth-century Byzantium, two foods with extreme opposite but equal flavored tastes: a sweet and a salty Arab product, paloudakin or apalodaton (fālūdhaj), which was the most typical sweet the Byzantines borrowed from the Arabs, and libysia, the especially flavorful salted fish from Egypt.